PENERAPAN PENYUSUNAN LAPORAN KEUANGAN MASJID NURUR RAHMAN TAMANAN, KABUPATEN BONDOWOSO BERDASARKAN ISAK NO 35 - Ulfha (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2022)
The research was conducted at the Nurur Rahman Tamanan mosque in Bondowoso. While the object of this research is the financial report of the Nurur Rahman mosque. The purpose of this study was to examine the arrangement of the budget summaries of the Nurur Rahman Tamanan Bondowoso Mosque in view of ISAK NO 35. Nurur Rahman Tamanan Mosque, Bondowoso is one of the institutions that is included as a Non-profit entity, which in its management requires making financial statements as a Form of accountability for funds. Which has been obtained. The financial statements of Non-profit entities include statements of financial position, statements of Comprehensive income, statements of net assets, statements of cash flows and notes to Financial statements. Included in the type of descriptive qualitative research. The data collection technique used in this research is to use observation, documentation and interviews. While the results of his research explain that the Nurur Rahman Tamanan Mosque is not in accordance with the current standards, namely ISAK NO 35 in making its financial statements